Creativity in the urban linguistic landscape as illustrated by signs of shops and service points - Miller, Dorota (Papers in Linguistics, 2025)
The superficial and fleeting contact of the audience with the message and the increasing textualisation of our surroundings mean that urban texts have the difficult role of capturing potential recipients’ attention amidst countless signs present in the public space. In reference to the growing linguistic exploration of so-called linguistic landscape, the aim of the article is to analyse commercial texts in the urban space of Rzeszów, gathered between February 2019 and February 2024. The research material consists of shop, restaurant and service point signs as minimal multimodal texts which shape the urban space and which have an attention-generating, informational and persuasive function. In contrast to official signs, they are characterised by a relatively high degree of compositional freedom and originality in terms of content and form. The article presents various examples of linguistic creativity understood as creating original, attractive, attention-grabbing linguistic constructions, often breaking the norms of linguistic correctness. The conducted analysis illustrates the extensive linguistic creativity manifesting itself on the ortho/typographic, word-formation, phraseological as well as intersemiotic and intertextual levels.